UJI EFEKTIVITAS EKSTRAK KULIT LANGSAT (Lansium domesticum) SEBAGAI ANTI NYAMUK ELEKTRIK TERHADAP NYAMUK Aedes aegypti (A Test onthe Effectiveness of Lansium Peel Extract (Lansium Domesticum) as Mosquito Electric Repellent Against Aedes aegypti Mosquitoes) - Mirnawaty, Mirnawaty; Supriadi, Supriadi; Jaya, Budiman (Universitas Tadulako, 2012)
The research concerning a test on the effectiveness of lansium peel extract (lansium domesticum) as a mosquito electric repellent against AedesAegypti mosquitoes has been done. This research aimed to know the effectiveness of lansium peelextractas anelectricmosquito repellent. The method used was laboratory experiments. The lansium peel extract obtained from the maceration method added with absolute methanol was evaporated to produce thick lansium peel extract. Then, the extract was diluted to the concentration of 35, 30, 25, 20, and 15%. The research data obtained was the death of aedes aegypti which then was analyzed by statistical varian analysis test (ANOVA) with the95% confidence level. It was followed by Duncan test to determine the most effective concentration. The result showed that the most effective concentration as electrical mosquitoes repellent was 25%.